Comparative genomic analysis of esophageal squamous cell carcinoma between Asian and Caucasian patient populations. Issue 1 (December 2017) - Deng, Jiaying; Chen, Hu; Zhou, Daizhan; Zhang, Junhua; Chen, Yun; Liu, Qi; Ai, Dashan; Zhu, Hanting; Chu, Li; Ren, Wenjia; Zhang, Xiaofei; Xia, Yi; et al.
Abstract Esophageal squamous cell carcinoma is a major histological type of esophageal cancer, with distinct incidence and survival patterns among races. Although previous studies have characterized somatic mutations in this disease, a rigorous comparison between different patient populations has not been conducted. Here we sequence the samples of 316 Chinese patients, combine them with those from The Cancer Genome Atlas, and perform a comparative analysis between Asian and Caucasian patients. We find that mutatedCSMD3 is associated with better prognosis in Asian patients. Applying a robust computational strategy that adjusts for both technical and biological confounding factors, we find thatTP53, EP300, andNFE2L2 show higher mutational frequencies in Asian patients. Moreover, NFE2L2 mutations correlate with the allele status of a nearby high-F st SNP, suggesting their potential interaction. Our study provides insights into the molecular basis underlying the striking racial disparities of this disease, and represents a general computational framework for such a cross-population comparison. Esophageal squamous cell carcinoma (ESCC) exhibits differences in incidence and survival patterns among races. Here, analysis of Chinese and TCGA ESCC patients reveals that Asian patients exhibit higher TP53, EP300 and NFE2L2 mutational frequencies, and mutated CSMD3 associates with better prognosis.